2022
DOI: 10.1155/2022/9294148
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-335-5p Contributes to Right Ventricular Remodeling via Calumenin in Pulmonary Arterial Hypertension

Abstract: Right ventricular (RV) failure determines the prognosis in pulmonary arterial hypertension (PAH), but the underlying mechanism is still unclear. Growing evidence has shown that microRNAs participate in RV remodeling. This study is undertaken to explore the role of miR-335-5p in regulating RV remodeling induced by PAH. Two PAH models were used in the study, including the monocrotaline rat model and hypoxia/su5416 mouse model. miRNA sequencing and RT-qPCR validation identified that miR-335-5p was elevated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Importantly, DME treatment recovered the expression of these miRNAs in 2K1C rats. In particular, let-7a-5p, miR-196b-5p, and miR-335-5p have been reported to be associated with hypertension, 36,37 which is in agreement with our study. However, as far as we know, the effects of miR-246-5p, miR-3557-3p, and miR-3596a on hypertension have not been reported yet.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, DME treatment recovered the expression of these miRNAs in 2K1C rats. In particular, let-7a-5p, miR-196b-5p, and miR-335-5p have been reported to be associated with hypertension, 36,37 which is in agreement with our study. However, as far as we know, the effects of miR-246-5p, miR-3557-3p, and miR-3596a on hypertension have not been reported yet.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the conservation score and correlation, miR-24-3p and miR-335-5p are expected to exhibit a stronger silencing action on VASH1 gene expression. Contrary to the data published on the upregulation of miR-335, 26,27 in hypertension and right ventricular remodeling and elevated levels of miR-24-3p levels in obese children with metabolic syndrome, positively correlated with various metabolic syndrome clinical parameters, including blood pressure. 28 further validation is warranted to define its role in adult-onset CV-TOI.…”
Section: Differential Expression Of Mirnas As Potential Post-transcri...contrasting
confidence: 99%
“…The latter study suggested miR-335-5p together with five other miRNAs as potential markers of deleterious left ventricular remodelling, but it did not provide evidence of changes in patients with established chronic heart failure. Studies in animal models have also related this miRNA with atherosclerosis [ 43 ] or ventricular remodelling [ 42 , 44 , 45 ], with apparently controversial findings. Thus, studies in mice have associated miR-335-5p overexpression with a reduction of atherosclerotic plaque vulnerability and angiogenesis promotion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studies in mice have associated miR-335-5p overexpression with a reduction of atherosclerotic plaque vulnerability and angiogenesis promotion [ 46 ]. In contrast, this miRNA was found up-regulated in rat and mouse models of pulmonary hypertension, where the induced right ventricular remodelling was linked to increased miR-335-5p expression and its blockade alleviated remodelling [ 45 ]. Interestingly, contrasting results were observed in a model of sepsis-induced myocardial injury [ 44 ].…”
Section: Discussionmentioning
confidence: 99%